(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes the characteristics of patriotism as one of the fundamental moral principles and one of the supporting pillars of every person’s spiritual inner world. It examines events and phenomena across various historical, socio-political, spiritual, and moral stages of our Homeland’s development.